Identification of Significant Compounds of Agarwood Incense Smoke Different Qualities using Z-Score - Nurlaila, Ismail; Mohd Hezri Fazalul, Rahiman; Mohd Nasir, Taib; Mastura, Ibrahim; Seema, Zareen; Saiful Nizam, Tajuddin (2015)
This paper presents the proposed Z-Score in identifying the significant chemical compounds of agarwood incense smoke. The technique is applied to commercial, low and high quality of agarwood samples and the extraction of the compounds were performed by gas chromatography - flame ion detector (GC-FID) and gas chromatography - mass spectrometry (GC-MS) coupled with solid phase microextraction (SPME) analysis. The Z-Score has successfully identified eight significant compounds in those qualities of agarwood smoke. They are β-maaliene, nor-ketoagarofuran, epoxybulnesene, 10-epi-γ-eudesmol, agarospirol, α-eudesmol, epi-α-bisabolol and rotundone. Among all, epoxybulnesene gave the highest abundant of 14.81%. The finding from this study showed that the chemical compounds for agarwood smoke is varied depending on their qualities. The identified compounds are useful for further study in agarwood smoke quality grading analysis.